Water resources handbook - Mays, Larry W. (McGraw-Hill, 1996)
This is the definitive reference on water resources management and issues. This handbook is by far the most comprehensive reference ever published on water resource issues. Written by the field's top experts, it presents authoritative information about a vast range of topics. It also brings into focus the many and increasingly complicated factors - involving not only engineering but also law, economics, finance, and public policy - the determine the quantity and quality of the world's potable water supply. No matter what your area of interest, if it concerns water resources you're likely to find it in this volume. Areas covered include: treatises on the state of the art in water resource economics and law policy-making and planning, and system analysis and risk analysis; quality management of natural systems such as lakes, reservoirs, rivers, groundwater, estuaries, and wetlands; water supply systems, including surface and groundwater, treatment and distribution, wastewater collection and treatment, water reuse, and water demand analysis; water excess management, including floodplain hydrology and hydraulics, urban stormwater, and flood control systems; the future impact of global climate change, water resources deficit management, decision support systems, and more; discussions of state-of-the-art computer models for water resources. For authoritative information that ranges from definitions and methodologies to guidelines and regulations - from the global to the specific - the "Water Resources Handbook" is the first place to look - now, and for years to come.